Looking for Improving the Urban Areas: the Case of Costa Rican Cantons in Their Path to Become Smart - Rodríguez Bolívar, Manuel Pedro (2024)
The process of becoming a smart city (SC) is still diffuse due to the contextual factors and urban challenges that local governments must face, so it is necessary to visualise new options and city strategies to implement them. This study contributes to prior research offering new insights concerning patterns used by small-sized cities in a developing and emerging country in the Latin American context (LATAM) in their early stages of becoming smart, analysing the dimensions to be developed, their pursued goals, their desired economic and/or social impacts, and the time frames expected to reach them. Our findings, based on cluster analysis and Kendall’s TAU C correlation, confirm differences in city strategies according to the contextual challenges faced by cities emphasising three different governance models to become smart based on the different significance given to the three components of the smart governance concept. The different city clusters point out different correlations among their priority goals and the smart dimensions, showing a different position of the cities in the smart dimensions’ development and goals. Also, differences in expected time frames to reach the aspired goals are identified. These findings allow us to derive new theoretical and managerial implications for cities on their path to become smart.